Photo‐Activity of Silacyclopropenes and their Application in Metal‐Free Curing of Silicones. Issue 3 (19th December 2022) - Nobis, Matthias; Futter, Jonas; Moxter, Maximilian; Inoue, Shigeyoshi; Rieger, Bernhard
Abstract: Silicone elastomers are usually produced via addition or condensation curing by means of platinum‐ or tin‐based catalysis. The employed catalysts remain in the final rubber and cannot be recovered, thus creating various economic and environmental challenges. Herein, a light‐mediated curing method using multifunctional silacyclopropenes as crosslinker structures was introduced to create an effective alternative to the conventional industrial crosslinking. To evaluate the potential of the photoreaction a model study with small monofunctional silirenes was conducted. These investigations confirmed the required coupling reactivity upon irradiation and revealed an undesired rearrangement formation. Further optimization showed the reaction selectivity to be strongly influenced by the substitution of the three‐membered ring system and the reaction temperature. The synthesis of multifunctional silirenes was described based on the most suitable model compound to create active crosslinker scaffolds for their application in silicone curing. This photo‐controlled process produces catalyst and additive free elastomers from liquid silicones, including hydride‐, hydroxy‐, or vinyl terminated polydimethylsiloxanes. Abstract : Curing agents : UV‐light mediated curing of polydimethylsiloxane is achieved via the utilization of multifunctional silacyclopropenes (silirenes) as photo‐active curing agents. A model study with small monofunctional silirenes is conducted to evaluate the photo‐reactivity and further optimize its crosslinking potential.